Web application user interface for customer relationship management in Spanish agritourism - Nazarov, Grigorii; Nguyen, Viet Bach; Dudáš, Marek; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Bachelor’s thesis focuses on the design and implementation of the user interface and user experience for a web application aimed at customer relationship management in Spanish agritourism. The primary objective is to create a responsive and visually ap-pealing front-end architecture that integrates with an existing backend system. This work forms a part of a larger project to develop a comprehensive digital solution for the agritourism sector. The proposed application addresses challenges faced by small and medium farms with limited digital accessibility by providing tools for farm profile management, event crea-tion, and visitor interaction. Insights for the development process are gathered through farm visits in Asturias, Spain, informal discussions with farmers, and an analysis of agri-cultural data to identify market trends and challenges. The front-end is developed using modern web technologies such as Vue.js, Nuxt 3, and Quasar to deliver a high-performing and user-friendly interface tailored to the specific needs of agritourism. The application is validated by user testing, providing valuable insights for future improvements and validating the application's functionality and intu-itiveness.
Vedoucí práce: Viet Bach Nguyen
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: informační média a služby [obor bakal. práce]; bakalářské práce; bachelor's theses